2003
DOI: 10.1306/071002730105
|View full text |Cite
|
Sign up to set email alerts
|

Microbialite Formation in Seawater of Increased Alkalinity, Satonda Crater Lake, Indonesia

Abstract: The crater lake of the small volcanic island Satonda, Indonesia, is unique for its red-algal microbial reefs thriving in marinederived water of increased alkalinity. The lake is a potential analogue for ancient oceans sustaining microbialites under open-marine conditions. Current reef surfaces are dominated by living red algae covered by non-calcified biofilms with scattered cyanobacteria and diatoms. Minor CaCO 3 precipitates are restricted to the seasonally flooded reef tops, which develop biofilms up to 500… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
186
0
7

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 202 publications
(203 citation statements)
references
References 87 publications
10
186
0
7
Order By: Relevance
“…Amorphous Mg-Si precipitates have previously been reported in carbonate environments, and are always associated with microbial activity [13][14][15] . It has also been demonstrated that am Mg-Si enhances fossilization, and is commonly found in the rock record 13 .…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Amorphous Mg-Si precipitates have previously been reported in carbonate environments, and are always associated with microbial activity [13][14][15] . It has also been demonstrated that am Mg-Si enhances fossilization, and is commonly found in the rock record 13 .…”
Section: Discussionmentioning
confidence: 96%
“…It has also been demonstrated that am Mg-Si enhances fossilization, and is commonly found in the rock record 13 . The authigenesis of am Mg-Si phases is, however, poorly understood, with previous work suggesting that am Mg-Si layers in microbialites are a replacement of a primary mineral phase 14 . In contrast, our data indicate a primary origin for these am Mg-Si phases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They can be laminated in the case of stromatolites. Although abundant in the Precambrian, microbialites are scarce today, being found only in restricted areas such as in the hypersaline Shark Bay in Australia (Logan, 1961) and in alkaline lakes such as Lake Van in Turkey (Kempe et al, 1991) or Lake Satonda in Indonesia (Arp et al, 2003). The stromatolites from the Bahamas are the only example of such structures developing in an open marine environment (Dravis, 1983;Dill et al, 1986;Reid and Browne, 1991;Reid et al, 2000Reid et al, , 2003.…”
Section: Introductionmentioning
confidence: 99%
“…Thereafter, examples of organominerals and organomineralization processes have been documented, and the former papers cited, in mainstream scientific literature, beginning with our own work on carbonate organomineral formation in modern and recent microbialites and ooids (Défarge et al, 1996;Reitner et al, 1997;Arp et al, 1999;Trichet et al, 2001;Arp et al, 2003;Gautret et al, 2004;Gautret and Trichet, 2005), ancient microbialite analogues (Camoin et al, 1999;Tribovillard et al, 1999Tribovillard et al, , 2000, mud mounds (Neuweiler et al, 1999), encrusting sponge cements (Russo et al, 2006), housing tubes of worms (Fischer et al, 2000), coral EPS (Reitner, 2005), decaying sponge tissues (Delecat et al, 2001), and during laboratory experiments with microbialite-, ooid-and meteorite-extracted organic matter (Reitner, 2004). Organominerals and organomineralization processes have also been brought up in a discussion, involving one of us, about the origin of lower Paleozoic carbonate mud (Pratt, 2001;Arp et al, 2002).…”
Section: Short History Of 'Organomineral' Definitionmentioning
confidence: 99%